ابتعاد طلاب الجامعات السعودیة عن استخدام المکتبات الجامعیة : دراسة تطبیقیة على جامعة الملک فیصل - د. أیمن مصطفى الفخرانى (المجلة الدولية لعلوم المكتبات والمعلومات)
The purpose of this research study was to investigate the usage of SaudiArabian university libraries.The research study also explored the reasons for non-usages of thelibrary services. Quantitative research design was used to fulfill the studyobjectives. The online survey questionnaire was used to collect the data fromcurrently enrolled students of King Faisal University, Saudi Arabia. Out of 700distributed questionnaires, 650 responded (93%) the survey.The results revealed that majority of students (71%) did not used or rarelyused the university library. The main reasons of underutilization were: lack ofmarketing of library services, non-availability information literacy program, noncooperativebehavior of library staff, and no library related assignments byteachers and complicated library policies.The study recommended that library should arranged formal usereducation program to educate students, make effective marketing of libraryresources and services, cooperative and welcoming library staff and user friendlylibrary policies .This is first study on King Faisal University library regarding use of libraryand bridges the gap in body of knowledge. The results of the study will be helpfulfor library staff, university administration and policy makers for improvement oflibrary services and future planning.